Highly pathogenic avian influenza virus H5N1 clade 2.3.4.4b in wild rats in Egypt during 2023 - Kutkat, Omnia; Gomaa, Mokhtar; Moatasim, Yassmin; El Taweel, Ahmed; Kamel, Mina Nabil; El Sayes, Mohamed; GabAllah, Mohamed; Kandeil, Ahmed; McKenzie, Pamela P.; Webby, Richard J.; Kayali, Ghazi; Ali, Mohamed Ahmed; et al. (Emerging microbes & infections, 2024)
We detected highly pathogenic avian influenza A(H5N1) virus in wild rats collected from a rural area in Giza, Egypt, near poultry farms, markets, and backyard flocks. Sequence and phylogenetic analyses indicated that the virus from the rats belonged to clade 2.3.4.4b, which has been the predominant virus genotype circulating in Egypt and worldwide since 2021-2022. Active surveillance of avian influenza viruses in wild and domestic mammals is recommended to prevent further spread to mammals and humans.